2017
DOI: 10.1111/jocn.13449
|View full text |Cite
|
Sign up to set email alerts
|

Correlates and predictors of missed nursing care in hospitals

Abstract: By identifying contributing factors to missed nursing care, appropriate interventions can be developed and tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
186
5
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(245 citation statements)
references
References 40 publications
19
186
5
15
Order By: Relevance
“…() who found that gender and age were not significantly associated with missed care. However, the result of the association of age with missed nursing care is congruent with the result of Bragadóttir and Kalisch () who found age to be a significant predictor of missed care. The results of the present study could be explained as nurses become older, they might perceive themselves as more experienced and competent and thus perceived committing reduced levels of missed care.…”
Section: Discussionsupporting
confidence: 82%
“…() who found that gender and age were not significantly associated with missed care. However, the result of the association of age with missed nursing care is congruent with the result of Bragadóttir and Kalisch () who found age to be a significant predictor of missed care. The results of the present study could be explained as nurses become older, they might perceive themselves as more experienced and competent and thus perceived committing reduced levels of missed care.…”
Section: Discussionsupporting
confidence: 82%
“…In the study of Bragadóttir et al, [13] the younger groups are also the ones that report more NCLU. There were differences between Gender in our study, like in Kalisch's study.…”
Section: Discussionmentioning
confidence: 88%
“…[9] In a South African study including 1,166 nursing professionals, NCLU were considered the major factor of job dissatisfaction. [12] A recently published article [13] analyzed the correlated factors and predictors of NCLU. These were directly related to the type of hospital and units, the age of the participants and their functions, as well as the perception of nurses about the appropriate number of nurses and the type of teamwork.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in ICUs of Iceland ( 33 ) also showed a positive but weak correlation between the number of patients and omission of care, that is, the more patients, the more activities may be missed. In addition, it also found that adequacy in staff sizing and improved teamwork diminish occurrences of missed or delayed care.…”
Section: Discussionmentioning
confidence: 99%